OUR EXPERIENCE WITH PEMETREXED/ CISPLATIN AS FIRST LINE CHEMOTHERAPY IN PATIENTS WITH ADVANCED NON- SQUAMOUS NON- SMALL CELL LUNG CANCER - Deyan N. Davidov (Peytchinski Publishing, 2013)
Objective: Lung cancer Pemetrexed is novel multitargeted antifolate which inhibits three key enzymes in the folate metabolic pathwaw. Methods: From May 2010 to March 2012 twenty two consecutive patients with morphologically proven advanced non- squamous non- small cell lung cancer entered the study. Treatment schedule consist of Pemetrexed 500 mg/m2 on day 1 and Cisplatin 80 mg/m2 with hyperhydratation administered as intravenous infusion with repetition every three weeks. Vitamins supplementation, antiemetics and Dexamethasone were administered too. Results: Overall response rate was 27,3 %, with one complete and five partial remissions obtained. The median time to progression and median overall survival time were 5,5 months and 9,6 months respectively. The main toxicity- grade 3 and 4, included neutropenia and diarrhea. Conclusions: That data suggest that chemotherapy with Pemetrexed / Cisplatin is reasonable choices for first- line chemotherapy in patients with inoperable non- squamous non- small cell lung cancer.